2016
DOI: 10.1073/pnas.1607074113
|View full text |Cite
|
Sign up to set email alerts
|

COP1 is required for UV-B–induced nuclear accumulation of the UVR8 photoreceptor

Abstract: The UV-B photoreceptor UV RESISTANCE LOCUS 8 (UVR8) promotes UV-B acclimation and tolerance in Arabidopsis thaliana. UVR8 localizes to both cytosol and nucleus, but its main activity is assumed to be nuclear. UV-B photoreception stimulates nuclear accumulation of UVR8 in a presently unknown manner. Here, we show that CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1) is required for UV-B-induced nuclear accumulation of UVR8, but bypassing the COP1 requirement for UVR8 nuclear accumulation did not rescue the cop1 mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
115
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 52 publications
8
115
0
Order By: Relevance
“…In Arabidopsis, the COP1-HY5 interaction has been well established (e.g. Ang et al, 1998); the interaction between COP1 and HY5 is UVB dependent: there is no interaction in the absence of photomorphogenic UVB (Favory et al, 2009;Yin et al, 2016). Therefore, our Y2H experimental data among CsUVR8, CsCOP1, and CsHY5 were consistent with findings in Arabidopsis, suggesting that cucumber may take a similar UVR8 signaling pathway for UVB stress responses.…”
Section: Yeast Two-hybrid Growth Assay Reveals Interaction Between Shsupporting
confidence: 84%
See 2 more Smart Citations
“…In Arabidopsis, the COP1-HY5 interaction has been well established (e.g. Ang et al, 1998); the interaction between COP1 and HY5 is UVB dependent: there is no interaction in the absence of photomorphogenic UVB (Favory et al, 2009;Yin et al, 2016). Therefore, our Y2H experimental data among CsUVR8, CsCOP1, and CsHY5 were consistent with findings in Arabidopsis, suggesting that cucumber may take a similar UVR8 signaling pathway for UVB stress responses.…”
Section: Yeast Two-hybrid Growth Assay Reveals Interaction Between Shsupporting
confidence: 84%
“…In Arabidopsis, it is well established that, under UVB, interaction of UVR8 with COP1 stabilizes HY5 (Favory et al, 2009;Huang et al, 2012;Cloix et al, 2012;Yin et al, 2015Yin et al, , 2016 and enhances the association of HY5 with target promoters, including its own (Oravecz et al, 2006;Abbas et al, 2014;Binkert et al, 2014). HY5 then activates transcription of many UVR8-regulated genes, which are associated with hypocotyl elongation inhibition, UVB protection, or acclamation (Brown et al, 2005;Oravecz et al, 2006;Huang et al, 2012;Binkert et al, 2014).…”
Section: Role Of Sh1 In Lduvb-dependent Hypocotyl Elongation: a Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants sense UV-B radiation via the homodimeric UV-B photoreceptor UV Resistance Locus 8 (UVR8) (21)(22)(23) that is mainly localized in the cytosol (24). Absorption of UV-B photons by intrinsic tryptophan residues leads to UVR8 monomerization, interaction with the E3 ubiquitin ligase Constitutively Photomorphogenic 1 (COP1), accumulation in the nucleus, and changes in gene expression (19,(21)(22)(23)(24)(25)(26)(27)(28)(29). After photoreception, UVR8 returns to the homodimeric ground state by redimerization (30,31).…”
mentioning
confidence: 99%
“…Heat and UV-B signaling systems(Box et al, 2015;Hayes et al, 2017;Quint et al, 2016;Yin et al, 2016) are, respectively, shown in red and purple (online only). Heat and UV-B signaling systems(Box et al, 2015;Hayes et al, 2017;Quint et al, 2016;Yin et al, 2016) are, respectively, shown in red and purple (online only).…”
mentioning
confidence: 99%